2018
DOI: 10.1016/j.athoracsur.2017.08.062
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Clinical Trial of Targeted Intraoperative Molecular Imaging for Pulmonary Adenocarcinomas

Abstract: This phase I trial provides preliminary evidence suggesting that folate receptor-targeted molecular imaging with OTL38 is safe, with tolerable grade I toxicity. These data also suggest that OTL38 accumulates in known lung cancers and may improve identification of synchronous malignancies. Our group is initiating a five-center, phase II study to better understand the clinical implications of intraoperative molecular imaging using OTL38.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 24 publications
2
72
0
Order By: Relevance
“…10 In our previous work, we have demonstrated that OTL38 binds the folate receptor with a high affinity, thus allowing for identification of synchronous disease in ∼10% of lung cancer patients and reproducible detection of subcentimeter nodules. 4,5 Based on our initial successes, we have hypothesized that this approach would be applicable to other pulmonary malignancies that express the FRα; however, the presented data herein are the first data to support this principle.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…10 In our previous work, we have demonstrated that OTL38 binds the folate receptor with a high affinity, thus allowing for identification of synchronous disease in ∼10% of lung cancer patients and reproducible detection of subcentimeter nodules. 4,5 Based on our initial successes, we have hypothesized that this approach would be applicable to other pulmonary malignancies that express the FRα; however, the presented data herein are the first data to support this principle.…”
Section: Discussionmentioning
confidence: 97%
“…This expression pattern is similar to our observations involving molecular imaging with OTL38 for pulmonary adenocarcinomas, and we have previously noted that tumor fluorescence is present even when as little as 20% to 30% of tumor expresses FRα. 5,11 As we continue enrollment of patients with osteosarcoma metastases in clinical trials, we will better understand how this expression pattern impacts the reproducibility of in vivo tumor fluorescence during pulmonary metastasectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the use of numerous drug-device combinations in preclinical and clinical studies, a definitive TBR threshold that indicates a positive fluorescent signal is difficult to define. However, successful intraoperative visualization of tumors has been demonstrated with several targeted agents that produce TBRs > 2 (30,38,39) and suggests that contrast ratios for Ga-MMC(IR800)-TOC may be sufficient for tumor identification in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…EC-17 is a small-molecule FITC based probe that was originally developed for fluorescence guided surgery (FGS) and has been shown to have high-affinity for FR+ CTCs previously [48]. Moreover, EC-17 and its NIR analog OTL-38 have both been used in FGS clinical trials [39,50], leading to the exciting possibility of using DiFC in humans in the future. Cy5-PEG-FR is a larger molecular weight probe, but has the advantage of having red excitation and emission wavelengths, which in principle is favorable for DiFC because of reduced optical attenuation of red light in biological tissue [49].…”
Section: Introductionmentioning
confidence: 99%